An Exploration of Facilitators and Challenges to Young Adult Engagement in a Community-Based Program for Mental Health Promotion. (May 2020) - Marie Creamer, Anne; Hughes, Jean; Snow, Nicole
Adolescence and young adulthood can be particularly daunting for those with mental health concerns. In one Canadian city, a community-based drop-in psychosocial mental health center (Center) was designed specifically for youth who self-identified as struggling with mental health issues. The purpose of this study was to identify the features of the program that promoted or discouraged engagement. Narrative inquiry was used to guide the project. One-on-one interviews were conducted with 10 Center users. Four major categories were identified: (a) Reasons for Coming: Motivated to Work on Goals; (b) Facilitators of Engagement and Beyond; (c) Challenges to Engagement; and (d) Benefits of Engaging: Finding My Way. These categories were further delineated into themes. All participants had experienced trauma, and the Center assisted them in their coping. The researchers believe that to aid recovery, agencies working with this population need to use trauma-informed and healing-centered engagement.